Penerapan Acceptable Quality Level (AQL) Dalam Tahapan Final Inspection Produk Garmen Di PT XYZ - Eki Wulandari Al Masruroh; Endang Pudji Widjajati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Quality control in the garment industry plays an important role to ensure that the products produced meet high quality standards and satisfy consumers. The Acceptable Quality Level method is a promising approach for optimizing garment product control. This research focuses on the application of the Acceptable Quality Level method in managing garment quality at PT XYZ. The aim is to explore the extent to which this method can be applied efficiently in garment production by considering the existing challenges and opportunities. This study uses the